Kecemasan Menghadapi Dunia Kerja pada Masa Depan di Kalangan Siswa SMK Blitar Jawa Timur - Binti Faridatul Awalia; Siti Mahmudah; Umdatul Khoirot (Jurnal Psikologi, 2023)
The problem of this research is the high anxiety of facing the employment future in Blitar Vocational High School students. This anxiety occurs because of the lack of social support from the family. Objective of this study was to determine the relationship between family social support and future anxiety among Blitar Vocational High School students. There were 61 students from 3 State Vocational Schools in Blitar. The results showed that the regression coefficient was -0.300 with a significance level of 0.009 (p <0.01) or very significant. This means that the stronger the family's social support, the lower the student's anxiety about the employment future.